Adaptive electronics for photovoltaic, photoluminescent and photometric methods in power harvesting for wireless wearable sensors - Chanho Park; Do Yun Park; Haohui Zhang; Da Som Yang; Catherine R. Redden; Seonggwang Yoo; Tae Wan Park; Mingyu Zhou; Jae-Young Yoo; Youngmin Sim; Abraham Vázquez-Guardado; Seung Yun Heo; et al. (Nature Communications)
Abstract The increasing demand for continuous, comprehensive physiological information captured by skin-interfaced wireless sensors is hindered by their relatively high-power consumption and the associated patient discomfort that can follow from the use of high capacity batteries. This paper presents an adaptive electronics platform and a tri-modal energy harvesting approach to reduce the need for battery power. Specifically, the schemes focus on sensors that involve light in their operation, through use of (i) photometric methods, where ambient light contributes directly to the measurement process, (ii) multijunction photovoltaic cells, where ambient light powers operation and/or charges an integrated battery, and (iii) photoluminescent packaging, where ambient light activates light-emitting species to enhance the first two schemes. Additional features of interest are in (i) in-sensor computational approaches that decrease the bandwidth and thus the energy consumption in wireless data communication and (ii) radio frequency power transfer for battery charging. These ideas have utility across broad other classes of wearable devices as well as small, portable electronic gadgetry.